CLASSIFICATION OF FACTORABLE SURFACES IN THE PSEUDO-GALILEAN SPACE - Aydin, Muhittin Evren; Ogrenmis, Alper Osman; Ergut, Mahmut (Croatian Mathematical Soc, 2015)
In this paper, we introduce the factorable surfaces in the pseudo-Galilean space G(3)(1) and completely classify such surfaces with null Gaussian and mean curvature. Also, in a special case, we investigate the factorable surfaces which fulfill the condition that the ratio of the Gaussian curvature and the mean curvature is constant in G(3)(1).
Keywords: Factorable surface; Gaussian curvature; mean curvature; minimal surface; pseudo-Euclidean plane; pseudo-Galilean space